A New Electrochemical Detection Technique for Organic Matter Content in Ecological Soils - Liu, Jinping; Yang, Tao; Xu, Jiaqi; Sun, Yankun (Frontiers in Chemistry, 2021)
The rapid detection of organic matter in soil is of great interest in agriculture, but the commonly used techniques require laboratory operation. Therefore, the development of a technique that allows rapid detection of soil organic matter in the field is of great interest. In this work, we propose an electrochemical-based approach for the detection of organic matter in soil particles. Since soil particles immobilized directly on the electrode surface can fall off during testing, we introduced graphene to coat the soil particles. The encapsulated soil particles can be stably immobilized on the electrode surface. We have investigated the electrochemical behavior of soil particles. The results show a correspondence between the electrochemical oxidation and reduction of soil particles and the organic matter content in them. We collected soil samples from three sites and constructed an electrochemical modeling, testing framework with stability based on multiple calibrations and random division of the prediction set. We used the equal interval partial least squares (EC-PLS) method for potential optimization to establish the equivalent model set. A joint model for the electrochemical analysis of organic matter in three locations of soil samples was developed for the commonality study.